STRATEGI HUMAS DIGITAL DALAM SOSIALISASI PROGRAM KAMPUS BERDAMPAK DI INSTAGRAM @DITJEN_DIKTI - Nisrina; Hudi Santoso (MEDIAKOM, 2025)
This study analyzed the digital public relations strategy of the Directorate General of Higher Education (Ditjen Dikti) in promoting the Kampus Berdampak program through its Instagram account @ditjen_dikti. The program, as a continuation of the Merdeka Belajar Kampus Merdeka (MBKM) policy, emphasized the real contribution of higher education to society. Using the POST framework (People, Objectives, Strategy, Technology), this research described how Ditjen Dikti designed an effective, participatory, and data-driven digital communication strategy. A qualitative descriptive method was applied through content observation, interviews, and literature studies conducted during an internship at Ditjen Dikti. The results showed that storytelling-based communication, interactive visual content, and the use of social media analytics successfully increased public awareness, engagement, and participation in the program. In conclusion, the implementation of the POST-based digital communication strategy effectively strengthened Ditjen Dikti’s image as a transparent, innovative, and socially impactful higher education institution.